Incorporation of a Benefit-Risk Assessment Framework Into the Clinical Overview of Marketing Authorization Applications. (January 2016) - Wolka, Anne; Warner, Margaret; Bullok, Kristin; Wang, JuAn; Radawski, Christine; Noel, Rebecca
Background: The main responsibility of regulators and industry is to ensure the benefit-risk balance of pharmaceutical products is positive for the intended patient populations. In recent decades, regulators and industry have taken steps to systematize benefit-risk decision making related to marketing authorization applications through the use of structured benefit-risk assessment. Methods: This manuscript presents an outline for a structured benefit-risk assessment that can be incorporated into Section 2.5.6 of the Clinical Overview to provide the basis for approval of pharmaceutical products in these regulatory submissions. Results: The structured format presents the benefits and risks of a pharmaceutical product in the context of the medical need in the disease state, the benefits and risks of available pharmacologic and nonpharmacologic therapies, and the approach for mitigating the risks of the product under review. Conclusions: Ultimately, such an approach that lends further support to quality decision making would be beneficial to patients who would be treated with new pharmaceutical products.